Fixed drug eruption to cetirizine with positive lesional patch tests to the three piperazine derivatives - Cravo, M (2010)
BACKGROUND: The H1-antihistamine cetirizine, a piperazine derivative widely used in daily practice, is rarely the cause of cutaneous drug reaction. Nevertheless, four cases of fixed drug eruption (FDE) as a result of this drug have been described recently. We present the case of a 45-year-old woman with a multilocalized FDE following oral intake of cetirizine for allergic rhinitis. METHODS: Patch testing with hydroxyzine 1% and 10% in petrolatum (Chemotechnique), and with powdered Zyrtec (cetirizine) and Xyzal (levocetirizine) pills, prepared at 20% in water and at 20% in petrolatum, was performed in both residual lesions and healthy skin. RESULTS: Positive results (++) to these drugs (24 h occlusion and readings at days 2 and 3) were obtained in residual lesions only. These results allowed us to confirm the drug responsible for this FDE and to study cross-reactions between antihistamines of the same chemical family. CONCLUSIONS: To the best of our knowledge, this is the first report of FDE to cetirizine with positive patch testing to hydroxyzine, cetirizine, and levocetirizine. This case highlights the importance of patch testing in the study of cutaneous drug reactions, namely FDE.